Kekerasan Epistemik Selama Covid-19 di Indonesia - Sanjaya, Angga Trio; Pramono, Dedi; Prasetya, Arif Budi (MIMESIS, 2024)
This research discusses epistemic violence against subaltern subjects who work through Western knowledge mechanisms so that all knowledge truths are measured using scientific and scientific schemes. The aim of this research is to understand the discourse of epistemic violence during the Covid-19 pandemic from Foucault's perspective through reading genealogy during the Covid-19 pandemic in information media from government websites and mass media. The research method in this study uses Foucault's discourse analysis which is based on the 'genealogy' method strategy to find an episteme that is converged with the term power-knowledge. The subject of this research is news discourse during Covid-19, while the object of this research is epistemic violence in news discourse during Covid-19. The news sources for this research are classified based on online media news texts which contain the production of knowledge discourse and regulations for handling Covid-19 which have the potential for epistemic violence. Data collection techniques in this research apply document review techniques, libraries, listening techniques and note-taking techniques. The research results show that there is epistemic violence perpetrated by the West against the East through discourses of knowledge and science during the spread and handling of Covid-19. This epistemic violence includes stereotype epistemic violence, discrimination epistemic violence, testimonial epistemic violence, distributional epistemic violence.